2010
DOI: 10.1177/1066896909349246
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Granulomatous Diseases and Granulomas of the Appendix

Abstract: Granulomatous appendicitis is a rare phenomenon. Idiopathic (primary) granulomatous appendicitis is very rare. It is a diagnosis by exclusion. There are many etiologies, both infectious and noninfectious, for secondary granulomatous appendicitis. Isolated appendiceal Crohn's disease (CD) is no longer an accepted explanation of idiopathic granulomatous appendicitis, but rather, it is thought to be part of more generalized gastrointestinal CD. Yersinia infection and CD constitute the main etiology of granulomato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 17 publications
1
55
0
2
Order By: Relevance
“…7 Although intestinal granulomas are rarely seen in typhoid fever, extraintestinal granulomatous changes have been documented (Ap pendix 1, available at www .cmaj .ca /lookup /suppl /doi :10.1503/cmaj.120714/-/DC1). Re ports of granulomas in the liver, bone marrow and spleen with typhoid fever have been published previously.…”
mentioning
confidence: 99%
“…7 Although intestinal granulomas are rarely seen in typhoid fever, extraintestinal granulomatous changes have been documented (Ap pendix 1, available at www .cmaj .ca /lookup /suppl /doi :10.1503/cmaj.120714/-/DC1). Re ports of granulomas in the liver, bone marrow and spleen with typhoid fever have been published previously.…”
mentioning
confidence: 99%
“…Treatment of GA is usually simple appendectomy, however some challenges may be shown in inflammatory bowel diseases, i.e. fistula in Crohn's disease [10]. In our study we performed ultrasound examination in all patients, however all examinations suspected only acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…A four-year review of 3381 appendectomy specimens showed only 13 cases (0.38%) of granulomatous appendicitis; of those, only one was believed to have been caused by TB. 9 Other infectious causes for a granulomatous appendix include infection with Yersinia enterocolitica and parasitic infections (such as strongyloidiasis and enterobiasis), whereas noninfectious causes include Crohn disease, sarcoidosis, diverticulitis and foreign body. 9 The treatment for appendicular TB is both surgical and medical.…”
Section: Discussionmentioning
confidence: 99%
“…9 Other infectious causes for a granulomatous appendix include infection with Yersinia enterocolitica and parasitic infections (such as strongyloidiasis and enterobiasis), whereas noninfectious causes include Crohn disease, sarcoidosis, diverticulitis and foreign body. 9 The treatment for appendicular TB is both surgical and medical. In conjunction with appendectomy, these patients must be given multiple antituberculous antibiotics as per standard guidelines.…”
Section: Discussionmentioning
confidence: 99%